Suicide Prevention in Adolescences: The Development and Evaluation of a Targeted Training Package - Monazah Zare Rashnudi; Mehrnaz Azadyekta; Bita Nasrolahi (Iranian Evolutionary Educational Psychology Journal)
Objective: This investigation was undertaken with the objective of formulating a training program aimed at the prevention of adolescent suicide and assessing its efficacy on suicidal ideation and impulsivity. Methods: The research methodology employed was semi-experimental, incorporating both experimental and control groups. The targeted demographic for this study comprised adolescent female students in their second year of high school in Tehran during the year 2023. A total of 60 students were selected from the aforementioned cohort and subsequently allocated into two groups of 30 individuals each (experimental and control) utilizing a simple random sampling technique. The instruments utilized for data collection included Beck's scale for suicidal ideation and the Barratt Impulsiveness Scale. In this investigation, a suicide prevention training package was conceptualized and developed grounded in two theoretical frameworks: acceptance and commitment therapy (ACT) and an emotion-focused approach (EFT). The data were subjected to analysis through the statistical procedure of multivariate analysis of covariance. Results: The findings indicated a statistically significant disparity in the levels of suicidal thoughts and impulsivity between the experimental and control groups in the post-intervention assessment. Accordingly, it can be inferred that the suicide prevention training package exerted a positive influence on the suicidal ideation and impulsivity among adolescents. Conclusions: This training package may serve as a valuable resource for psychologists and counselors engaged in providing support services to adolescent populations.